Continuous left hemidiaphragm sign revisited: a case of spontaneous pneumopericardium and literature review. Issue 4 (1st October 2002) - Brander, L; Ramsay, D; Dreier, D; Peter, M; Graeni, R
Abstract : In pneumopericardium, a rare but potentially life threatening differential diagnosis of chest pain with a broad variety of causes, rapid diagnosis and adequate treatment are crucial. In upright posteroanterior chest radiography, the apical limit of a radiolucent rim, outlining both the left ventricle and the right atrium, lies at the level of the pulmonary artery and ascending aorta, reflecting the anatomical limits of the pericardium. The band of gas surrounding the heart may outline the normally invisible parts of the diaphragm, producing the continuous left hemidiaphragm sign in an upright lateral chest radiograph. If haemodynamic conditions are stable, the underlying condition should be treated and the patient should be monitored closely. Acute haemodynamic deterioration should prompt rapid further investigation and cardiac tamponade must be actively ruled out. Spontaneous pneumopericardium in a 20 year old man is presented, and its pathophysiology described.